Dampak Keberadaan Objek Wisata Tebing Breksi terhadap Kehidupan Sosial Ekonomi Masyarakat di Desa Sambirejo, Prambanan, Kabupaten Sleman - Mona Erythrea Nur Islami (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
The research aims to determine the socio-economic conditions of the community in Sambirejo village before existing of tourism activities and after. The research is a qualitative study used to describe a situation or phenomenon. The method of collecting data uses observation and interviews with tourism actors directly involved in tourism activities on Tebing Breksi and are affected economically and socially. The result showed that the existence of Tebing Breksi had a positive effect on the socio-economic changes for the community of Sambirejo village. The economic impact is the creation of job and business opportunities, increased community income, CBT based management and accelerated infrastructure development. Social impact is the emergence of new livelihood structures in tourism and gives positive value transformation